2006
DOI: 10.1021/jo052411+
|View full text |Cite
|
Sign up to set email alerts
|

Is [N+−H···O] Hydrogen Bonding the Most Important Noncovalent Interaction in Macrocycle−Dibenzylammonium Ion Complexes?

Abstract: We report a new host molecule in which one diethylene glycol chain (i.e., a loop possessing only three oxygen atoms) incorporated along with two phenolic aromatic rings is linked by a xylene spacer into a macroring. The design of the molecular structure of this macrocycle "amplifies" any potential [cation...pi], [N+-H...pi], and [N+C-H...pi] interactions between the dibenzylammonium (DBA+) ion and the phenolic rings of the macrocycle; as such, these species display a very strong binding affinity in CD3NO2 (Ka … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(12 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…Several cagelike structures, in addition to modified cryptophanes, , have been probed and display great ability to hold cations in their cavities. Tran et al reported the synthesis of zorbarene, which has a calixarene-like structure, and showed how the tetramethylammonium cation has relatively strong association constants suggesting stronger cation−π mediated interactions with these hosts . Synthesis of cage-type molecules composed of phenyl walls and caps as hosts for the binding of ammonium and alkali metal cations through cation−π interactions has also been reported .…”
Section: Cation−π Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several cagelike structures, in addition to modified cryptophanes, , have been probed and display great ability to hold cations in their cavities. Tran et al reported the synthesis of zorbarene, which has a calixarene-like structure, and showed how the tetramethylammonium cation has relatively strong association constants suggesting stronger cation−π mediated interactions with these hosts . Synthesis of cage-type molecules composed of phenyl walls and caps as hosts for the binding of ammonium and alkali metal cations through cation−π interactions has also been reported .…”
Section: Cation−π Interactionsmentioning
confidence: 99%
“…This study suggests a gate-selective binding process in case of binding with Li + and NH 4 + ions and not the cavity size of the cage type molecules as a guiding factor. Studies on host molecules in which one diethylene glycol chain is incorporated along with two phenolic aromatic rings linked by a xylene spacer into a macrocycle reveal how this design serves to enhance any potential cation−π, N + –H···π and N + C–H···π interactions between the dibenzylammonium ion and the phenolic rings of the macrocycle . C 3 -symmetric macro-tricycles built from π electron-rich resorcinol show a preferential recognition of NH 4 + over K + , along with a poor response to the larger t -BuNH 3 + cation, suggesting that NH 4 + binds intramolecularly via cation−π interactions .…”
Section: Cation−π Interactionsmentioning
confidence: 99%
“…The last decade witnessed rapid expansion of various interesting interlocked molecular architectures with controllable binding sites (stations), reversible shuttling behavior, and even rate-tunable properties. Control of the sophisticated ring-thread interactions under different chemical environments lies at the heart of rational design of those novel molecular shuttles with desired functions and activities. Some general relationship of the site-specific interactions has been recognized on the basis of numerous experimental and theoretical calculations. Relative displacements and binding positions of the macrocycle on thread can be detected by a variety of techniques, such as NMR, absorption and emission, and electrochemical spectroscopy. For the complicated rotaxane systems in solution, however, it is hard to unambiguously assign those spectra due to the conformational flexibility of rotaxane and subtle perturbations from the surrounding solvent molecules.…”
Section: Introductionmentioning
confidence: 99%
“…In theory, such a dual-mode molecular switch could be constructed by adding two more recognition stations to the thread component of a [2]rotaxane, allowing the interlocked macrocyclic moiety to migrate specifically in the presence of a particular charged species (see abstract image); because these ions cannot be added to the solution without complementary counterions, however, fine-tuning of the energetics would be required to maintain the orthogonality of the two operating modes. Herein, we report a three-station [2]rotaxane in which 2,2′-bipyridyl and carbamate units serve as additional recognition stations that allow the bis- p -xylyl-[26]crown-6 (BPX26C6) component to migrate away from its originally occupied guanidinium station upon the addition and removal of Zn 2+ and PO 4 3– ions, respectively.…”
mentioning
confidence: 99%